Exploring Marine natural products as potential Quorum sensing inhibitors by targeting the PqsR in Pseudomonas aeruginosa: Virtual screening assisted structural dynamics study - Manikandan Jayaraman; Vijayakumar Gosu; Rajalakshmi Kumar; Jeyakanthan Jeyaraman; Hak-kyo Lee; Donghyun Shin (PLoS ONE, 2025)
Antibiotic resistance is a critical global health issue, and Pseudomonas aeruginosa is a particularly challenging pathogen. This gram-negative bacterium is notorious for its high virulence and resistance to antimicrobial agents, making it a leading cause of nosocomial infections, significantly impacting public health. The adaptability and multidrug resistance of P. aeruginosa exacerbate treatment difficulties, resulting in increased morbidity and mortality rates worldwide. Consequently, targeting bacterial quorum sensing (QS) systems is a promising strategy for the development of novel antimicrobial compounds against this resilient pathogen. In this study, a structure-based virtual screening (SBVS) approach was employed to identify marine natural products (MNPs) as potential lead molecules targeting the biofilm-forming PqsR protein of P. aeruginosa. A total of ~37,000 MNPs were initially evaluated and ranked based on docking scores using high-throughput virtual screening (HTVS), Standard Precision (SP), and Extra Precision (XP) methods. Ten lead molecules (five from the CMNPD database and five from the MNPD database) were shortlisted based on their docking scores (<−10.0 kcal/mol) and binding free energy values (MM-GBSA ΔG <−40 kcal/mol). Their drug-likeness profiles were assessed using stringent criteria in the QikProp module of Schrödinger, and their chemical reactivity was evaluated through density functional theory (DFT) calculations. The structural and energetic interactions between the identified MNPs and the PqsR-binding pocket were validated through molecular dynamics simulations (MDS) and binding free energy (BFE) calculations. Structural dynamic analyses revealed that the MNP-bound PqsR complexes demonstrated stable interactions within the binding pocket, with hydrophobic residues such as L208, I236, and I263 playing a crucial role in maintaining stability. Among the identified MNPs, CMNPD14329, CMNPD23880, MNPD13399, and MNPD13725 emerged as promising lead molecules for further research. These candidates can serve as foundations for developing structural analogs with enhanced binding affinities for PqsR and other biofilm-forming proteins. Further experimental validation is essential to confirm the therapeutic potential of these identified MNPs.